Why am I here? engaging the reluctant client - McVeigh, Lynne; Tisch School of the Arts. Undergraduate Film/Television Dept.; Council on Social Work Education ([New York, N.Y.] : New York University : Distributed by Council on Social Work Education, 2002)
"Why I am here? features two 20-minute vignettes in which social work students interview reluctant clients and then debrief with a supervisor. Based on actual process recordings of student sessions, the vignettes realistically portray the experience of social work interns working with new clients who resist their interventions"--Container.
DVD.
Closed-captioned
Keywords: Social work education; Social service -- Vocational guidance; Interviewing in social service; Video recordings for hard of hearing people